The Role of FLOWERING LOCUS C Relatives in Cereals - Kennedy, Alice; Geuten, Koen (Frontiers in Plant Science, 2020)
FLOWERING LOCUS C (FLC) is one of the best characterized genes in plant research and is integral to vernalization-dependent flowering time regulation. Yet, despite the abundance of information on this gene and its relatives in Arabidopsis thaliana, the role FLC genes play in other species, in particular cereal crops and temperate grasses, remains elusive. This has been due in part to the comparative reduced availability of bioinformatic and mutant resources in cereals but also on the dominant effect in cereals of the VERNALIZATION (VRN) genes on the developmental process most associated with FLC in Arabidopsis. The strong effect of the VRN genes has led researchers to believe that the entire process of vernalization must have evolved separately in Arabidopsis and cereals. Yet, since the confirmation of the existence of FLC-like genes in monocots, new light has been shed on the roles these genes play in both vernalization and other mechanisms to fine tune development in response to specific environmental conditions. Comparisons of FLC gene function and their genetic and epigenetic regulation can now be made between Arabidopsis and cereals and how they overlap and diversify is coming into focus. With the advancement of genome editing techniques, further study on these genes is becoming increasingly easier, enabling us to investigate just how essential FLC-like genes are to modulating flowering time behavior in cereals.